A phase III randomized study of first-line NUC-1031/cisplatin vs. gemcitabine/cisplatin in advanced biliary tract cancer - Knox, Jennifer J.; McNamara, Mairéad G.; Bazin, Igor S.; Oh, Do-Youn; Zubkov, Oleksii.; Breder, Valeriy; Bai, Li-Yuan; Christie, Alan; Goyal, Lipika; Cosgrove, David P.; Springfeld, Christoph; Sjoquist, Katrin M.; et al. (Journal of hepatology, 2025)
Background & Aims - The previous first-line standard of care for advanced biliary tract cancer (aBTC), gemcitabine/cisplatin, has modest efficacy. NUC-1031 is a phosphoramidate modification of gemcitabine. We report final analyses of the NuTide:121 study, designed to compare the efficacy of NUC-1031/cisplatin to gemcitabine/cisplatin in aBTC. - Methods - In this open-label, multicenter study, adult patients with treatment-naïve aBTC were randomized (1:1) to NUC-1031/cisplatin (n = 388) or gemcitabine/cisplatin (n = 385) on Days 1 and 8 of 21-day cycles until disease progression or intolerance. Primary endpoints were overall survival (OS) and objective response rate (blinded independent central review). Three interim analyses (IA) and a final analysis were planned. - Results - Baseline characteristics were balanced; median age 65 years, 53% male, primary tumors: intrahepatic cholangiocarcinoma (CCA) (54%), extrahepatic CCA (21%), gallbladder cancer (21%) and ampullary cancer (5%). Enrollment stopped at IA1 as the OS futility boundary was crossed. At final data cut-off, median OS for NUC-1031/cisplatin vs. gemcitabine/cisplatin was 9.2 months (95% CI 8.3-10.4) vs. 12.6 months (95% CI 11.0-15.1) (HR 1.79) and median PFS was 4.9 months (95% CI 4.4-6.0) vs. 6.4 months (95% CI 6.1-7.4) (HR 1.45). Objective response rate was higher for NUC-1031/cisplatin (18.7% vs. 12.4%; OR: 1.59; p = 0.049). The adverse event profile was similar between arms, except for hepatobiliary disorders (25% vs. 11%; higher with NUC-1031/cisplatin) and hematological events (48% vs. 65%; higher with gemcitabine/cisplatin). More patients met criteria for potential drug-induced liver injury (27% vs. 7%) and Hy’s law (1.6% vs. 0.5%) with NUC-1031/cisplatin. Treatment exposure was lower for NUC-1031/cisplatin, likely due to early discontinuation for AEs (30% vs. 18%). - Conclusions - NuTide:121 was terminated early due to futility. NUC-1031/cisplatin did not set a new standard in first-line aBTC. - Impact and implications - Although clinical practice guidelines identified gemcitabine plus cisplatin as standard of care for advanced biliary tract cancer (aBTC) based on clinical studies, the modest efficacy observed with this regimen highlighted the urgent need for more effective therapies. NuTide:121, one of the largest randomized interventional studies conducted in the first-line aBTC population to date, compared the combination of cisplatin with NUC-1031, a phosphoramidate form of gemcitabine, with the standard of care regimen. Despite a higher response rate in the NUC-1031/cisplatin arm, the study was terminated early based on a futility assessment for OS. Early toxicity and in particular liver injury likely contributed to the regimen's failure. This study emphasized some important challenges in study design and further confirmed the difficulties of advancing treatment options in this vulnerable patient population. - Trial Registration - ClinicalTrials.gov Identifier: NCT04163900.
Gesehen am 12.01.2026